Effects of three recovery protocols on range of motion, heart rate, rating of perceived exertion, and blood lactate in baseball pitchers during a simulated game - Warren, C. D.; Szymanski, D. J.; Landers, M. R. (The Journal of Strength and Conditioning Research, 2015)
Baseball pitching has been described as an anaerobic activity from a bioenergetics standpoint with short bouts of recovery. Depending on the physical conditioning and muscle fiber composition of the pitcher as well as the number of pitches thrown per inning and per game, there is the possibility of pitchers fatiguing during a game, which could lead to a decrease in pitching performance. Therefore, the purpose of this study was to evaluate the effects of 3 recovery protocols: passive recovery, active recovery (AR), and electrical muscle stimulation (EMS) on range of motion (ROM), heart rate (HR), rating of perceived exertion (RPE), and blood lactate concentration in baseball pitchers during a simulated game. Twenty-one Division I intercollegiate baseball pitchers (age = 20.4 ± 1.4 years; height = 185.9 ± 8.4 cm; weight = 86.5 ± 8.9 kg; percent body fat = 11.2 ± 2.6) volunteered to pitch 3 simulated 5-inning games, with a maximum of 70 fastballs thrown per game while wearing an HR monitor. Range of motion was measured pre, post, and 24 hours postpitching for shoulder internal and external rotation at 90° and elbow flexion and extension. Heart rate was recorded after each pitch and after every 30 seconds of the 6-minute recovery period. Rating of perceived exertion was recorded after the last pitch of each inning and after completing each 6-minute recovery period. Immediately after throwing the last pitch of each inning, postpitching blood lactate concentration (PPLa-) was measured. At the end of the 6-minute recovery period, before the next inning started, postrecovery blood lactate concentration (PRLa-) was measured. Pitchers were instructed to throw each pitch at or above 95% of their best-pitched fastball. This was enforced to ensure that each pitcher was throwing close to maximal effort for all 3 simulated games. All data presented represent group mean values. Results revealed that the method of recovery protocol did not significantly influence ROM (p > 0.05); however, it did significantly influence blood lactate concentration (p < 0.001), HR (p < 0.001), and RPE (p = 0.01). Blood lactate concentration significantly decreased from postpitching to postrecovery in the EMS recovery condition (p < 0.001), but did not change for either the active (p = 0.04) or the passive (p = 0.684) recovery conditions. Rating of perceived exertion decreased from the postpitching to postrecovery in both the passive and EMS recovery methods (p < 0.001), but did not decrease for AR (p = 0.067). Heart rate decreased for all conditions from postpitching to postrecovery (p < 0.001). The use of EMS was the most effective method at reducing blood lactate concentration after 6 minutes of recovery during a simulated game (controlled setting). Although EMS significantly reduced blood lactate concentrations after recovery, blood lactate concentrations after pitching in the simulated games were never high enough to cause skeletal muscle fatigue and decrease pitching velocity. If a pitcher were to throw more than 14 pitches per inning, throw more total pitches than normal per game, and have blood lactate concentrations increase higher than in the simulated games in this study, the EMS recovery protocol may be beneficial to pitching performance by aiding recovery. This could potentially reduce some injuries associated with skeletal muscle fatigue during pitching, may allow a pitcher throw more pitches per game, and may reduce the number of days between pitching appearances.